Artificial intelligence and future of health care-doctors’ perspective: an exploratory qualitative study - Rani, M. Usha; Vemparala, Sai Shanmukh (International Journal of Research in Medical Sciences, 2024)
Background: This exploratory study investigates the perspectives of medical professionals on the integration of artificial intelligence (AI) in healthcare. It focuses on key areas such as diagnostics, drug development, patient care, and medical information management. Methods: The study utilizes a qualitative survey approach, engaging a diverse group of doctors to understand their views on AI’s benefits and limitations. The methodology includes analyzing responses and categorizing them into themes of optimism, skepticism, and the perceived need for a human touch in patient care. Results: Results indicate a cautiously optimistic view of AI among medical professionals, acknowledging its potential to enhance healthcare efficiency and accuracy. However, the results also highlight concerns about over-reliance on technology, data privacy, and potential biases. Conclusions: The study concludes that while AI presents significant opportunities for healthcare innovation, its integration demands a balanced approach. This balance is essential for leveraging AI’s capabilities while synergizing with the irreplaceable human aspects of medical practice, ensuring patient-centered care, and maintaining the core values of the medical profession.